If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 8 + -2y = 3y + -6 + 5y Reorder the terms: 8 + -4y + -2y = 3y + -6 + 5y Combine like terms: -4y + -2y = -6y 8 + -6y = 3y + -6 + 5y Reorder the terms: 8 + -6y = -6 + 3y + 5y Combine like terms: 3y + 5y = 8y 8 + -6y = -6 + 8y Solving 8 + -6y = -6 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 8 + -6y + -8y = -6 + 8y + -8y Combine like terms: -6y + -8y = -14y 8 + -14y = -6 + 8y + -8y Combine like terms: 8y + -8y = 0 8 + -14y = -6 + 0 8 + -14y = -6 Add '-8' to each side of the equation. 8 + -8 + -14y = -6 + -8 Combine like terms: 8 + -8 = 0 0 + -14y = -6 + -8 -14y = -6 + -8 Combine like terms: -6 + -8 = -14 -14y = -14 Divide each side by '-14'. y = 1 Simplifying y = 1
| x+1.7=3 | | f(x)=x^2+12x+40 | | 4.2-n=16 | | (13x+11)*(7x+41)=0 | | 11+(-3)= | | (x+2)(x+3)+(x+4)(x+5)=24 | | (3y-8)(9+y)=0 | | 62+3x=9x-6 | | 2x^4+y^4=98 | | 2x^2+y^2=10 | | -15+(15)= | | 48+6x=4-9x | | 7x=5x+42 | | -3+(12)= | | 3+b=-5 | | e^3x+1=10 | | -y+6=8 | | p-6=15 | | z=x-43/9 | | 2z-19=-27+6x | | 6x-23=-7+2x | | x^9+y^6=36 | | (x^2/25)^1/2 | | 0.5714=0.08333x | | 2=200/x^2 | | n-m=6 | | 4/7=x/12 | | x^2+y^2+2x-16y=16 | | (2x+7)=(3x+3) | | x/7=63/x | | 17-4(6x-2)=-3 | | 3x^2+10x-13=17-3x |